2000
DOI: 10.1002/(sici)1096-9888(200002)35:2<210::aid-jms931>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the carbohydrate composition and the disulfide bond linkages of bovine lactoperoxidase by mass spectrometry

Abstract: The extent and distribution of N‐glycosylation and the nature of most of the disulfide bond linkages were determined for bovine lactoperoxidase through proteolytic and glycolytic digestions combined with matrix‐assisted laser desorption/ionization mass spectrometric analysis. In addition, 98% of the primary sequence of the protein was confirmed. All five of the asparagines present in sequons were found to be glycosylated, predominantly by high mannose and complex structures. Six disulfide bonds were assigned, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
2
30
2
Order By: Relevance
“…However, as LPS is a glycoprotein that contains almost 10% carbohydrate, such an heterogeneity may also be related to the type of carbohydrate attached to the enzyme by glycosylation. In fact, Wolf, Ferrari, Traversa, and Biemann (2000) reported that the glycosylation sites of LPS are fully occupied with different high mannose and complex structures and this may vary molecular weight of LPS between 74,850 and 79,188 Da.…”
Section: Partial Purification Of Lpsmentioning
confidence: 99%
“…However, as LPS is a glycoprotein that contains almost 10% carbohydrate, such an heterogeneity may also be related to the type of carbohydrate attached to the enzyme by glycosylation. In fact, Wolf, Ferrari, Traversa, and Biemann (2000) reported that the glycosylation sites of LPS are fully occupied with different high mannose and complex structures and this may vary molecular weight of LPS between 74,850 and 79,188 Da.…”
Section: Partial Purification Of Lpsmentioning
confidence: 99%
“…Using this strategy, it has been shown that the nonoccupancy of the three glycosylation sites in a plasma protein, α1-antitrypsin, from CDG-I patients was not random but determined by structural features [89,90]. A similar strategy has also been successfully used to determine the extent and distribution of N-glycosylation in bovine lactoperoxydase [91].…”
Section: A Mald-msmentioning
confidence: 99%
“…One of those compounds is the enzyme lactoperoxidase. [14] Lactoperoxidase (LPO; EC 1.11.1.7) is a heme-containing glycoprotein with a single chain of 612 residues. LPO contains about 10% carbohydrate and its molecular mass is approximately 78 kDa.…”
Section: Introductionmentioning
confidence: 99%